PEMBINAAN DINAS TATA RUANG KOTA PEKANBARU DALAM PENYELENGGARAAN PEMBANGUNAN GEDUNG DI KECAMATAN TENAYAN RAYA 2011-2013 - Elviza "; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background of this research with theThe existence of absorption wells is one of theprocedures that must be completed to the requirements of development shop. Absorption wellsis very important for the shop building, where a very positive function in absorbing water.With so can anticipate floodwaters around the shop building. The existence of infiltrationwells are not all owned by the owner of the shop building.The method used in this study qualitative research methods. Data collection techniquesin research, interviews, search documentation, observation. Source of data in this study areprimary data and secondary data.Based on the results of research conducted in the Department of City Spatialpengasawan Pekanbaru in coaching and guidance isGiven the organization of the building tofit Pekanbaru City Regional Regulation No. 7 of 2012 on Building Permits.Empowerment bySpatial Agency Pekanbaru through socialization by holding seminars to all district head,headman, associations, government offices and private se Pekanbar City, Spatial Agency alsoput ads on the radio RRI, and the Department of Spatial Pekanbaru installing billboardsplaces general.Supervision maximum is not done by the Department of Spatial PekanbaruCity for human resources are not adequate to conduct surveillance, minimal funding sourcesto conduct supervision and coaching, then the low level of public awareness of governmentregulations. Inhibiting Spatial Agency Pekanbaru in fostering human resources areinadequate to conduct training and supervision, as Spatial Agency only had 14 people incharge of doing the coaching and supervision. Lack of budget owned Spatial Agency therebyinhibiting to conduct supervision and guidance to the building that violates the rules and donot have permission. Lack of public awareness about the importance of regulatory pemerintato complete the building permit and also build in accordance with the existing rules.Keywords: Development, Spatial Planning, Organizing, Building